Semiconductor Quantum Dots for Integrated Quantum Photonics (Adv. Quantum Technol. 9/2019). Issue 9 (11th September 2019) - Hepp, Stefan; Jetter, Michael; Portalupi, Simone Luca; Michler, Peter
Abstract : The cover image shows an artistic impression of a fully on‐chip quantum photonic circuit based on semiconductor quantum dots (QDs) as nonclassical light sources. The QDs are directly integrated within a network of waveguides, beam splitters and phase shifters for the passive and active manipulation of the quantum states of light. The integrated superconducting nanowire single‐photon detectors make the on‐chip detection of single photons feasible. For further information see the review by Stefan Hepp and co‐workers, article number1900020 . (Image design by S. Kolatschek.)